2013
DOI: 10.1371/journal.pone.0071083
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Population Genetic Structure in Yelloweye Rockfish (Sebastes ruberrimus) Is Consistent with a Major Oceanographic Division in British Columbia, Canada

Abstract: The boundaries between oceanographic domains often function as dispersal barriers for many temperate marine species with a dispersive pelagic larval phase. Yelloweye rockfish (Sebastes ruberrimus, YR) are widely distributed across the northeastern Pacific Ocean, inhabiting coastal rocky reefs from the Aleutian Islands in Alaska through southern California. This species exhibits an extended pelagic larval duration and has the capacity for long distance larval transport. We assayed 2,862 YR individuals from 13 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Regardless of whether deacon rockfish were organized into nearshore and offshore groups, morphological and genetic differences were statistically significant but small among the sample sites. Although our morphometric and genetic results were comparable to findings from other marine fishes sampled over larger geographic distances (Benestan et al, ; Berg et al, ; Lee et al, ; Libungan et al, ; Soeth et al, ), previous stock assessment using similar methods has relied upon stronger patterns in data to delineate a stock boundary (Siegle, Taylor, Miller, Withler, & Yamanaka, ; Ward, ).…”
Section: Discussionsupporting
confidence: 81%
“…Regardless of whether deacon rockfish were organized into nearshore and offshore groups, morphological and genetic differences were statistically significant but small among the sample sites. Although our morphometric and genetic results were comparable to findings from other marine fishes sampled over larger geographic distances (Benestan et al, ; Berg et al, ; Lee et al, ; Libungan et al, ; Soeth et al, ), previous stock assessment using similar methods has relied upon stronger patterns in data to delineate a stock boundary (Siegle, Taylor, Miller, Withler, & Yamanaka, ; Ward, ).…”
Section: Discussionsupporting
confidence: 81%
“…Although Cape Flattery and Puget Sound itself have both been classified as biogeographic barriers due to a bifurcation in ocean currents (Kelly & Palumbi, ; Valentine, ), there are surprisingly few studies evaluating the genetic structure of species found both within Puget Sound and on the outer coast of Washington. Those that do focus on species with much longer dispersal times than O. lurida (Buonaccorsi, Kimbrell, Lynn, & Vetter, ; Cunningham, Canino, Spies, & Hauser, ; Iwamoto et al., ; Jackson & O'Malley, ; Siegle, Taylor, Miller, Withler, & Yamanaka, ). To my knowledge, this is the first study in a marine mollusk to evaluate and identify significant population differentiation among Puget Sound populations and the outer coast.…”
Section: Discussionmentioning
confidence: 99%
“…Although Cape Flattery and Puget Sound itself have both been classified as biogeographic barriers due to a bifurcation in ocean currents (Valentine, 1966; Kelly and Palumbi, 2010), there are surprisingly few studies evaluating the genetic structure of species found both within Puget Sound and on the outer coast of Washington. Those that do focus on species with much longer dispersal times than O. lurida (Buonaccorsi et al, 2002; Cunningham et al, 2009; Iwamoto et al, 2015; Siegle et al, 2013; Jackson and O’Malley, 2017). To my knowledge, this is the first study in a marine mollusc to evaluate and identify significant population differentiation among Puget Sound populations and the outer coast.…”
Section: Discussionmentioning
confidence: 99%